Changes in modified Glasgow prognostic score after neoadjuvant chemotherapy is a prognostic factor in clinical stage II/III esophageal cancer. Issue 2 (17th December 2014) - Otowa, Yasunori; Nakamura, Tetsu; Takiguchi, Gosuke; Tomono, Ayako; Yamamoto, Masashi; Kanaji, Shingo; Imanishi, Tatsuya; Suzuki, Satoshi; Tanaka, Kenichi; Itoh, Tomoo; Kakeji, Yoshihiro
Summary: The inflammation‐based modified Glasgow prognostic score (mGPS) has been shown to be a prognostic factor for esophageal cancer, but its changes in relation to neoadjuvant chemotherapy (NAC) have never been discussed. The purpose of this study was to evaluate the potential prognostic role of mGPS with regard to NAC. mGPS was evaluated on the basis of admission blood samples taken before chemotherapy and before surgery. Patients with elevated C‐reactive protein (CRP) serum levels (>10 mg/L) and hypoalbuminemia (<35 g/L) were allocated a score of 2, patients with elevated CRP serum levels without hypoalbuminemia were allocated a score of 1, and patients with normal CRP serum levels with or without hypoalbuminemia were allocated a score of 0. A total of 100 patients with clinical stage II/III squamous cell esophageal cancer, who underwent NAC and esophagectomy between January 2007 and August 2012, were investigated. From the multivariate analysis, the grade of response to chemotherapy and post‐NAC mGPS level was found to be independent prognostic factors. The overall survival rate was significantly higher in the conserved mGPS group than in the worse mGPS group ( P = 0.030). Changes in mGPS during chemotherapy affected the prognosis of patients, and post‐NAC mGPS is an independent prognostic factor in patients with clinical stage II/III thoracic esophageal squamous cell cancer.